2018
DOI: 10.1002/jia2.25142
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of HIV home‐based counselling and testing rounds in Western Kenya

Abstract: IntroductionWeaknesses in care programmes providing anti‐retroviral therapy (ART) persist and are often instigated by late HIV diagnosis and poor linkage to care. We investigated the potential for a home‐based counselling and testing (HBCT) campaign to be improved through the optimal timing and enhancement of testing rounds to generate greater health outcomes at minimum cost.MethodsUsing a mathematical model of HIV care calibrated to longitudinal data from The Academic Model Providing Access To Healthcare (AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…
We appreciate the letter in response to our article "Optimal timing of HIV home-based counselling and testing rounds in Western Kenya [1]. " The authors appraise the assumptions made by the model and question whether the modelled HBCT programme in western Kenya could be improved [2].As the authors are aware, high prevalence settings often require active outreach to identify a meaningful proportion of the infected population [3].
…”
supporting
confidence: 72%
See 1 more Smart Citation
“…
We appreciate the letter in response to our article "Optimal timing of HIV home-based counselling and testing rounds in Western Kenya [1]. " The authors appraise the assumptions made by the model and question whether the modelled HBCT programme in western Kenya could be improved [2].As the authors are aware, high prevalence settings often require active outreach to identify a meaningful proportion of the infected population [3].
…”
supporting
confidence: 72%
“…We appreciate the letter in response to our article "Optimal timing of HIV home-based counselling and testing rounds in Western Kenya [1]. " The authors appraise the assumptions made by the model and question whether the modelled HBCT programme in western Kenya could be improved [2].…”
mentioning
confidence: 99%
“…A modelling study of an HBCT campaign in western Kenya showed that in 20 years, DALYs averted could be maximised with a so-called front-loaded scenario, whereby four testing rounds are delivered in years 1, 2, 4, and 8, compared with a scenario of five equally spaced rounds every 4 years. 42 More research is needed exploring alternative and sustainable approaches to HIV test provision, including initial door-to-door testing followed by mobile or hub-based testing, self-testing, 43 , 44 or potentially decreasing the frequency of door-to-door testing.…”
Section: Discussionmentioning
confidence: 99%